2004
DOI: 10.1017/s004727940400772x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Gender Regimes and Policies for Gender Equality in a Wider Europe

Abstract: This article addresses some implications for gender equality and gender policy at European and national levels of transformations in family, economy and polity, which challenge gender regimes across Europe. Women's labour market participation in the west and the collapse of communism in the east have undermined the systems and assumptions of western male breadwinner and dual worker models of central and eastern Europe. Political reworking of the work/welfare relationship into active welfare has individualised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
191
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(200 citation statements)
references
References 42 publications
1
191
0
8
Order By: Relevance
“…The different patterns found among women in these dual breadwinner typologies can be explained by the reduction in the support for families and children in a range of areas in Eastern European countries: family allowance, nursery provision, sick child leave, and parental benefits (28,44). Moreover, traditional family values are much more common in post-communist countries than Western industrialized countries (29). Since long working hours were more frequent among married women, work conflict and overload derived from the double burden of job and family demands could partly explain our findings (45,46).…”
Section: Artazcoz Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The different patterns found among women in these dual breadwinner typologies can be explained by the reduction in the support for families and children in a range of areas in Eastern European countries: family allowance, nursery provision, sick child leave, and parental benefits (28,44). Moreover, traditional family values are much more common in post-communist countries than Western industrialized countries (29). Since long working hours were more frequent among married women, work conflict and overload derived from the double burden of job and family demands could partly explain our findings (45,46).…”
Section: Artazcoz Et Almentioning
confidence: 99%
“…However, within the family, traditional ways of constructing men and women's roles remain. Moreover, the economic damage to state revenues has undermined the social policies that supported them as workers and mothers (28,29).…”
mentioning
confidence: 99%
“…There is still gender inequality concerning the distribution of paid and unpaid work between women and men as well as equal payment for equal work. In their research, Pascall and Lewis (2004) demonstrated that equal treatment across the five levels of political intervention (voice, paid work, incomes, care work, time) has not been achieved in any of the European countries studied. Sanchez de Madariaga (2013: 329) argues that 'recognizing and making visible unpaid work in the city, giving and effectively improving the physical environment in which it is performed, can be a powerful means for transforming gender relations in the longer term, above and beyond providing short term improvement to women's lives'.…”
mentioning
confidence: 96%
“…Yet, despite the publication of seminal books on masculinity by Bly (2001) and Keen (1992), no studies by male entrepreneurship scholars specifically tackle the masculinity-entrepreneurship interface (Burns, 1991). Pascall and Lewis (2004) identified voice as a key element of gender regimes. Thus, I…”
mentioning
confidence: 99%